Impact of hypertension on long-term humoral and cellular response to SARS-CoV-2 infection - Chu, Chang; Schönbrunn, Anne; Klemm, Kristin; von Baehr, Volker; Krämer, Bernhard K.; Elitok, Saban; Hocher, Berthold (Frontiers in Immunology, 2022)
It was shown that hypertension delays SARS CoV-2 viral clearance and exacerbates airway hyperinflammation in the respiratory tract. However, it is unknown whether hypertension determines the long-term cellular and humoral response to SARS Cov2. Health care workers (HCWs) after an outbreak of SARS Cov-2 infections were analyzed. Infected HCWs were not vaccinated before blood collection. 5-14 months (median 7 months) after detection of SARS CoV-2 infection, blood was taken to analyze humoral response (S1 IgG and SARS CoV-2 neutralizing antibodies) and cellular (T cell responses to SARS-CoV-2 with Lymphocyte Transformation Test). To identify clinical factors that determine the immune response, a multivariant regression analysis was done considering age, BMI, sex, diabetes, hypertension, smoking, COPD, asthma and time between PCR positivity and blood collection as confounding factors. Infected hypertensive HCWs more often developed anosmia, myalgia and needed to be hospitalized as compared to non-hypertensive HCWs. The long-term humoral and cellular immune response was significantly strengthened in hypertensive versus normotensive infected HCWs. Multivariant regression analysis revealed that only hypertension but not age, BMI, sex, diabetes, smoking, COPD, asthma and time between PCR positivity and blood taking was independently associated with the humoral and cellular response to SARS CoV-2 infection. In conclusion, SARS CoV-2 infection strengthened humoral and cellular immune response to SARS CoV-2 infection in hypertensive HCWs independent of other risk factors and also severity of symptoms.